Perubahan Sosial Dalam Olahraga - Yonathan Lukar; Resky Resky (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Social change in sports reflects the transformation occurring in the structure, values, and dynamics of society through sports activities. Sports, as a social phenomenon, not only serve as a means of recreation and competition but also as an important instrument in influencing social aspects such as integration, gender equality, social mobility, and solidarity. Social changes brought about by sports manifest in various forms, including shifts in norms and values that promote inclusivity, diversity, and broader participation. Issues such as human rights, anti-discrimination, and gender equality are increasingly gaining attention in the modern sports world. Additionally, technological advancements and globalization have accelerated changes in the way sports are practiced and consumed by society. This leads to new opportunities, such as increased access to sports across different social strata, but also presents new challenges, including commercialization and inequality in access to quality sports facilities. Thus, sports become both a reflection and a catalyst for broader social change dynamics within global society.